Monks, Monasteries, and Muslim Scribes: Three Parchment House Sales from the 4th/10th-Century Fayyūm - Vanthieghem, Naïm (Arabica, 2020)
This article presents editions of three Arabic parchment deeds of sale from the 4th/10th-century Fayyūm Oasis belonging to two monks, Babā Banīla and Babā Buṭrus, of the Dayr al-Qalamūn monastery. The transactions recorded in our documents are mundane in and of themselves. But put together they offer bits of insight into Christian society in rural medieval Egypt, the notarial practice of provincial Muslim scribes, the relationship between monastic and Islamic legal institutions, and the important but little-attested Dayr al-Qalamūn.